The Influence Between Working Capital and Profitability Company (Study at Food and Beverage Sector listed at Indonesia Stock Exchange for 2008-2011 period) - ElvaJulnine, Hesvibet; wati, Andar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to examine the relationship of working capital management and profitability company in food and beverage sector listed at Indonesia Stock Exchange. In order to know the relationship occur among the independent variable (Inventory Conversion Period, Days Sales Outstanding, Payable Deferral Period, and Cash Conversion Cycle) on Return on Asset using the regression analysis, F test and t Test was conducted. This research is explanatory research, in accordance with its purpose to explain the correlation and relations of some fixed variables. The sample in this research were the income statement and statement of cash flows dataÂ from Food and Beverage sector listed at Indonesia Stock Exchange. The sampling technique is Purposive sampling and the research instruments tested using classical assumption test. The hypothesis testing was using the F and t test to analyze the data to be used in Multiple Regression Analysis. The multiple regression showed that, simultaneously and partially tested Inventory Conversion Period, Days Sales Outstanding, Payable Deferral Period, and Cash Conversion Cycle. While the dominant tes shows cash conversion cycle has dominant affecting to Return on Assets. Â Keywords; Inventory Conversion Period, Days Sales Outstanding, Payable Deferral Period, and Cash Conversion Cycle, and Return on Assets